2005
DOI: 10.1126/science.1118313
|View full text |Cite
|
Sign up to set email alerts
|

Glial Membranes at the Node of Ranvier Prevent Neurite Outgrowth

Abstract: Nodes of Ranvier are regularly placed, nonmyelinated axon segments along myelinated nerves. Here we show that nodal membranes isolated from the central nervous system (CNS) of mammals restricted neurite outgrowth of cultured neurons. Proteomic analysis of these membranes revealed several inhibitors of neurite outgrowth, including the oligodendrocyte myelin glycoprotein (OMgp). In rat spinal cord, OMgp was not localized to compact myelin, as previously thought, but to oligodendroglia-like cells, whose processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
133
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(142 citation statements)
references
References 31 publications
5
133
4
Order By: Relevance
“…For example, axons produce aberrant branches without the inhibitory effects of myelin. 52 The ordered arrangement of ion channels at the nodes of Ranvier (and therefore conductive properties of axons) also critically depends on correct myelination. 53 Oligodendrocytes are considered to be essential to long-term axonal integrity, potentially through trophic support mechanisms and axon−glia metabolic coupling mechanisms 54,55 leading to a widely held view that axon− myelin interactions have an important neuroprotective role (and by extension impact disease progression when perturbed).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For example, axons produce aberrant branches without the inhibitory effects of myelin. 52 The ordered arrangement of ion channels at the nodes of Ranvier (and therefore conductive properties of axons) also critically depends on correct myelination. 53 Oligodendrocytes are considered to be essential to long-term axonal integrity, potentially through trophic support mechanisms and axon−glia metabolic coupling mechanisms 54,55 leading to a widely held view that axon− myelin interactions have an important neuroprotective role (and by extension impact disease progression when perturbed).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Interestingly, Nogo and NgR1 appear to play a role in closing the period of ocular dominance plasticity in mice (McGee et al, 2005). Furthermore, OMgp functions to restrict axonal sprouting from the Nodes of Ranvier as discussed above (Huang et al, 2005). Both of these two functions are in line with a general role in axonal plasticity for these neurite inhibitors in the absence of an injury.…”
Section: Physiological Function Of the Nogo/ngr1 Pathwaymentioning
confidence: 81%
“…Initially thought to be present in compact myelin, it was later shown that OMgp is expressed in the membrane surrounding the Nodes of Ranvier made by oligodendrocyte-like cells (Huang et al, 2005). Furthermore, most of OMgp expression appears to be in the neurons (Habib et al, 1998).…”
Section: Omgpmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps these mechanisms operate on different spatial scales, with the PDGF signal operating over long distances to generally stimulate proliferation in an active axon fibre tract, while the glutamate signal is more spatially localised (due to efficient uptake by transporters) and inhibits proliferation when OPCs form a close apposition with an axon. If glutamate release from myelinated axons (Kriegler and Chiu, 1993) occurs from nodes of Ranvier, it might serve to tonically repress proliferation of OPCs, which have processes contacting the nodes (Butt et al, 1999) apparently in order to prevent axonal sprouting at that point (Huang et al, 2005). The glutamate released by action potentials may also regulate OPC migration (Wang et al, 1996;Gudz et al, 2006).…”
mentioning
confidence: 99%